Pengaruh pemaafan terhadap kesejahteraan psikologis remaja tanpa peran ayah - Ashillah Mahira Dina Desya Putri; Siti Maimunah (Universitas Muhammadiyah Malang, 2026)
Psychological well-being plays an important role in adolescent growth. Adolescents at a psychologically vulnerable age need the full support of their parents, especially their fathers. The purpose of this study was to determine the effect of forgiveness on the psychological well-being of adolescents without a father’s involvement. This study used a quantitative approach with convenience sampling. The data used in this study were collected from 299 respondents using Mccullough’s Transgression Related InterpersonalMotivation Scale (TRIMS-18) and Ryff and Keyes’ Psychological Well-Being Scale. Data analysis was performed using simple linearregression tests. The results of this study show that there is a significant effect of forgiveness on the psychological well-being of adolescents without father’s involvement, with a significance value of p=0,000 (p=<0,05) and an R Square of 0.166. The findings from this study indicate that forgiveness plays a role as a psychological factor that can support the improvement of psychological well-being in adolescents who grow up without a father figure. Therefore, the results of this study are expected to serve as a basis for consideration inthe development of psychological counseling and intervention for adolescents in similar circumstances.